2018
DOI: 10.1002/path.5012
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived, metastatic urothelial cancer after kidney transplantation associated with a potentially oncogenic BK polyomavirus

Abstract: BK polyomavirus has been linked to urothelial carcinoma in immunosuppressed patients. Here, we performed comprehensive genomic analysis of a BK polyomavirus-associated, metachronous, multifocal and metastatic micropapillary urothelial cancer in a kidney transplant recipient. Dissecting cancer heterogeneity by sorting technologies prior to array-comparative genomic hybridization followed by short tandem repeat analysis revealed that the metastatic urothelial cancer was of donor origin (4-year-old male). The top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…However, also in these cancer cells the BKPyV‐integration process seems to be accompanied by changes in the viral genome precluding viral replication. In particular loss of VP1 coding sequence and deletions in the NCCR have been described . In one case, such a deletion which was present both in an episomal and integrated viral genome was shown to confer decreased viral replication capacity but increased T‐antigen expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, also in these cancer cells the BKPyV‐integration process seems to be accompanied by changes in the viral genome precluding viral replication. In particular loss of VP1 coding sequence and deletions in the NCCR have been described . In one case, such a deletion which was present both in an episomal and integrated viral genome was shown to confer decreased viral replication capacity but increased T‐antigen expression .…”
Section: Discussionmentioning
confidence: 99%
“…In particular loss of VP1 coding sequence and deletions in the NCCR have been described. 43,44 In one case, such a deletion which was present both in an episomal and integrated viral genome was shown to confer decreased viral replication capacity but increased T-antigen expression. 43 Similarly, increased T-antigen expression has also been described for clinically occurring NCCR rearrangements in HPyV7 and HPyV9.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most serious complication of BKV in these patients is the development of urologic malignancies. Fortunately, such complications are rare and only 36 cases of urothelial carcinoma (UC) (Table ), and several renal cell carcinomas, including collecting duct carcinomas were reported to date …”
Section: Discussionmentioning
confidence: 99%
“…However, recent genomic studies have suggested, or at least produced findings consistent with, the idea that BK polyomavirus may contribute to tumorigenesis through viral integration into the host genome and expression of viral oncoproteins (e.g. polyoma T‐antigen) . From the standpoint of the differential diagnosis with bona fide CDC, our experience with ongoing studies of a cohort of these tumors is that they most frequently are urothelial carcinomas; however, they often show variant differentiation, which can include glandular patterns entering the differential diagnosis with CDC (Fig.…”
Section: Differential Diagnoses and Emerging Entitiesmentioning
confidence: 99%
“…Anecdotal experience suggests that such cases may show a more urothelial pattern of differentiation, sometimes with “glassy” nuclear changes suggestive of viral cytopathic effect, with expression of markers such as GATA3 and p63, diffuse nuclear p53, and diffuse IHC expression using antibodies against T‐antigen . Recognition of the phenomenon is important, given better established therapy for urothelial carcinoma compared to CDC, and given reports of resolution of even metastatic disease upon cessation of immunosuppression . We suspect that with increasing scholarship and experience, BK‐related tumors with infiltrative glandular pattern that have been considered CDC previously would come to be excluded from this group.…”
Section: Differential Diagnoses and Emerging Entitiesmentioning
confidence: 99%